The Oxford handbook of Roman Egypt - Riggs, Christina (Oxford handbooks in archaeology, 2012)
Roman Egypt is a critical area of interdisciplinary research, which has steadily expanded since the 1970s and continues to grow. Egypt played a pivotal role in the Roman empire, not only in terms of political, economic, and military strategies, but also as part of an intricate cultural discourse involving themes that resonate today - east and west, old world and new, acculturation and shifting identities, patterns of language use and religious belief, and the management of agriculture and trade. Roman Egypt was a literal and figurative crossroads shaped by the movement of people, goods, and ideas, and framed by permeable boundaries of self and space